ID 178 – Longitudinal simultaneous DBS fMRI in the rodent brain. Issue 3 (March 2016) - Van Den Berge, N.; Vanhove, C.; Descamps, B.; Dauwe, I.; van Mierlo, P.; Raedt, R.; Vonck, K.; Boon, P.; Van Holen, R.
Abstract : Objective: The effects of Deep Brain Stimulation (DBS) have been studied primarily by electrophysiological and neurochemical studies, which lack the ability to elucidate DBS-related responses on a whole-brain scale. With this study our aim is to investigate DBS-induced global neuronal network activation in rats with functional Magnetic Resonance Imaging (fMRI). Methods: Three times FMRI was done in seven rats, which were stereotactically implanted with a MR-compatible DBS-electrode in the right hippocampus. High frequency Poisson distributed stimulation was applied using a block-design paradigm. Response maps ( p  < 0.05) were obtained with Independent Component Analysis. Results: Our data indicate that real-time hippocampal DBS evokes a uni- or bilateral BOLD response in hippocampal and mesolimbic structures, depending on the applied stimulation intensity. Results were reproducible in time and in-between subjects. Conclusions: We present that DBS-fMRI can be used to detect whole-brain responses to circuit activation with different stimulation intensities, making this technique potentially powerful for exploring DBS-induced cerebral changes for preclinical and clinical DBS. Key message: A better understanding of the whole-brain effect of DBS is necessary to improve treatment efficacy in patients. Successful translation of this research to patients might reduce the number of non-responders to this invasive and expensive treatment.